Hubungan Kepatuhan Konsumsi Tablet Fe Terhadap Kejadian Anemia - Yuni Handayani; Ilyas Arif Budiman (Oksitosin : Jurnal Ilmiah Kebidanan, 2022)
The government's steps to reduce maternal mortality and infant mortality is starting from adolescence by giving blood tablets to young women. It is necessary to understand the knowledge of young women about the importance of nutrition fulfillment and regular consumption of Fe tablets. This study aims to analyze the relationship between adherence to Fe tablet consumption and the incidence of anemia in Mumbulsari Village, Jember Regency in 2021. The research design used in this study was a correlational analytic study with a cross sectional research approach. With sample of 50 respondents who meet the inclusion criteria with purposive sampling technique. The data analysis used in this research is univariate analysis, bivariate analysis with Spearman's Rho correlation. It was found that 62.% of female adolescents did not consume Fe tablets, 66% of female adolescents experienced anemia, and the results of cross tabulation showed that female adolescents did not comply in consuming Fe tablets and experienced anemia of 78.8%. The results of the data analysis test using a Spearman's Rho p-value less than the value of , it is stated that there was a relationship between adherence to consuming Fe tablets with the incidence of anemia in adolescent girls in Mumbulsari District, Jember Regency in 2021. It is recommended that there be collaboration between health workers, schools and people parents to monitor adolescent girls to comply with taking Fe tablets regularly.